USING OF REMOTE SENSING FOR MONITORING GEOMORPHOLOGICAL TEOMPRAL CHANGES FOR TIGRIS RIVER IN BAGHDAD CITY - & et al., Muhaimeed (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2017)
Tigris River was chosen as astudy area in Baghdad province to study the geomorphological temporal changes due to the effect of erosion and deposition by remote sensing .Normalized Difference Suspended Sediment Index (NDSSI) was calculated by data of Landsat 7 and 8 for +ETM and OLI ,respectively , between 1989 and 2014. Ten sites were selected within five regions represent all geomorphologic forms in the study area starting from Altajee to Alga’ara site located between the longitude 44° 19´ 50.512" E, 33° 23´ 24.754" N and 44° 32´ 07.762" E , 33° 09´ 21.432" N, with distance of 59945 m. The results indicated that there is a difference in the activity of geomorphologic processes associated with the movement of the Tigris River in Baghdad province, particularly sculpture and sedimentation processes. It was easy to find the existence of activity of sedimentation, especially in some curves that have helped to reduce the movement factor of the carrier sediments speed, and the results showed a significant contrast in the sedimentary material area between the selected sites during the study period in the year 2014 than it was in 1989. The results indicated there is an inverse relationship between the sediment guide values and deposits outstanding.